THE INFLUENCE OF SOCIAL MEDIA ON MODERN ENGLISH VOCABULARY - Abdullayeva Niginabonu Akmaljon qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This study investigates the impact of social media on modern English vocabulary, focusing on the creation of new words, slang, and abbreviations. Social media platforms such as Twitter, TikTok, Instagram, and Reddit accelerate language change, enable rapid dissemination of lexical innovations, and promote global hybridization of English. Findings show that new words often originate in specific online communities and quickly gain widespread usage, reflecting the decentralized and dynamic nature of digital language. Statistics from 2023 indicate that over 1,200 new slang terms appeared on TikTok alone, with approximately 65% spreading to other platforms within a month (Crystal, 2004; Coleman, 2014; Zappavigna, 2012).